Testing urban edge effects: Nest predation rates are higher in areas further from the boundary of a suburban park - Ailun Wang; Tara J. Pirie; Mark D.E. Fellowes (Avian Research)
Urban green spaces and parks offer opportunities for retaining and increasing bird richness, diversity, and species abundance. However, urbanisation influences predator–prey interactions, leading to high predation rates in urban areas, in the UK notably through the presence of large populations of domestic cats and increased populations of synanthropic species, such as rats and squirrels. These high predation rates are assumed to be a significant cause of reproductive failure in birds. Some ecologists advocate for the use of buffer zones with reduced human influence to reduce potential hunting pressure in eco-sensitive areas. However, the buffer effect on predation rates of nesting birds in suburban areas is rarely investigated. In this study, we investigated how edge effects (how close nest sites are to housing) and nest height (i.e., ground vs. above-ground) affected nest predation rates in a suburban park using camera traps to monitor artificial nests containing quail eggs. Our hypothesis was that nests in the buffer area (<300 m inward from university boundary) and at low height would suffer higher predation rates than nests in the core area (>300 m from the university boundary) and at height, as the buffer zone effect, and ease of access to ground predators would result in higher predation rates. We found no significant effect of nest height in nest predation rates. However, contrary to our expectations, nests in the core zone suffered higher predation rates than those in the buffer zone, and corvids were responsible for almost half of the egg loss events. We speculate that this may be a consequence of higher levels of anthropogenic disturbance (e.g., pedestrians, dog walking, vehicles) adjacent to our buffer zone acting as a deterrent to avian nest predators. This work suggests that protecting urban sites from disturbance may not always act to support bird abundance.